Rescue procedures in the major trauma of upper extremities - The role of the polish medical air rescue in the therapeutic process - Robert Gałązkowski; Stanisław Paweł Świeżewski; Daniel Rabczenko; Arkadiusz Wejnarski; Dariusz Timler; Grzegorz Michalak; Ireneusz Kotela (Nofer Institute of Occupational Medicine, 2014)
Background: Due to the growing use of various types of industrial and agricultural machinery, occupational accidents are among the most serious ones and quite frequently result in the permanent posttraumatic disability of the injured person. In Poland, a replantation service has been operating since 2010. Each day, one out of six centres provides emergency replantation service accepting amputation calls from across the country. Patients qualified for replantation often need to be transported from places located even several hundred kilometres from the target hospital. Material and Methods: The analysis covered 174 Helicopter Emergency Medical Service (HEMS) missions and 112 interhospital transports. The data were obtained as a result of a retrospective analysis of the air and medical documentation of 23 460 missions carried out by the Polish Medical Air Rescue (Samodzielny Publiczny Zakład Opieki Zdrowotnej Lotnicze Pogotowie Ratunkowe - SP ZOZ LPR) aircrafts in the years 2011-2013. Results: In the period under study, the Polish Medical Air Rescue helicopters dressed 135 patients with upper extremity amputations at the scene and transported them to hospitals as part of HEMS missions. At the same time, SP ZOZ LPR aircrafts made 102 interhospital transports. Ninety patients were qualified for treatment in replantation service centres. The average air transport time was 76 min, while the total transport time was 172.3 min. With transport exceeding 300 km, the average time advantage over the ground transport was approximately 1.5 h. Conclusions: In justified cases, the use of helicopters and airplanes is an optimal method of transporting patients with the major trauma to upper extremities. Med. Pr. 2014;65(6):765-776